Constitutional Change in the European Union Towards a Federal Europe - Duff, Andrew (Springer Nature, 2022)
Europe's future is contested between those who want to integrate further, those who prefer things to stay as they are, and those who would retreat into nationalism. These divisions impair the government of the European Union and weaken its ability to shoulder more responsibility for its unstable neighbourhood. This open access book analyses the EU's evolving constitution, arguing that the lack of effective federal government lies at the heart of its problems. It recommends reforms for each EU institution, including those involving treaty change. It makes the case for a unified executive, a more legitimate legislature, and the introduction of a federal treasury and supreme court. It proposes a fresh category of affiliate membership underpinned by a new European security council that would overcome the historic division between the EU and NATO. The book is essential reading for practitioners and students of European integration.